Defects in early synaptic formation and neuronal function in Prader-Willi syndrome - Shuhei Soeda; Daiki Ito; Tomoe Ogushi; Yui Sano; Ryosuke Negoro; Takuya Fujita; Ryo Saito; Hideo Taniura (Scientific Reports, 2023)
Abstract Prader-Willi syndrome (PWS), which is a complex epigenetic disorder caused by the deficiency of paternally expressed genes in chromosome 15q11-q13, is associated with several psychiatric dimensions, including autism spectrum disorder. We have previously reported that iPS cells derived from PWS patients exhibited aberrant differentiation and transcriptomic dysregulation in differentiated neural stem cells (NSCs) and neurons. Here, we identified SLITRK1 as a downregulated gene in NSCs differentiated from PWS patient iPS cells by RNA sequencing analysis. Because SLITRK1 is involved in synaptogenesis, we focused on the synaptic formation and function of neurons differentiated from PWS patient iPS cells and NDN or MAGEL2 single gene defect mutant iPS cells. Although βIII tubulin expression levels in all the neurons were comparable to the level of differentiation in the control, pre- and postsynaptic markers were significantly lower in PWS and mutant neurons than in control neurons. PSD-95 puncta along βIII tubulin neurites were also decreased. Membrane potential responses were measured while exposed to high K+ stimulation. The neuronal excitabilities in PWS and mutant neurons showed significantly lower intensity than that of control neurons. These functional defects in PWS neurons may reflect phenotypes of neurodevelopmental disorders in PWS.